Relationship of Parenting to Personal Hygiene Independency of Children Aged 5 To 6 Years - Mutia Wulandari; Ismaniar Ismaniar (Universitas Negeri Padang, 2021)
This research was motivated by the low personal hygiene independence of children's 5-6 years age in Jorong Batu Kijang, Nagari Dilam, Bukit Sundi District, Solok. This is thought to be one of the reasons because parental care at home is less than optimal. This study aims to determine whether there is a significant relationship between parental care and personal hygiene independence of children aged 5-6 years in Jorong Batu Kijang, Nagari Dilam, Bukit Sundi District, Solok. This research is a correlational quantitative research. A sample of 25 people was determined by using a simple random sampling technique from a population of 35 people. The results of the study were analyzed using the Spearman rank formula. Based on the results and processing of research data, it can be concluded that: a) parental care in Jorong Batu Kijang is not well implemented; b) the personal hygiene independence of children aged 5-6 years in Jorong Batu Kijang is categorized as less independent; c) there is a significant relationship between parental care and personal hygiene independence for children aged 5-6 years in Jorong Batu Kijang, Nagari Dilam, Bukit Sundi District, Solok. It is recommended to 1) parents to pay attention to good parenting to increase the independence of children's personal hygiene; and 2) early childhood education institutions to provide basic knowledge about children's personal hygiene and parenting methods to parents of early childhood that can be applied to train children's self-reliance at home.